Pleomorphic xanthoastrocytoma - Jagtap, Sunil V.; Gupta, Sonal O.; Jokhi, Cyrus Dara; Jagtap, Swati S. (International Surgery Journal, 2017)
Pleomorphic Xanthoastrocytomas (PXAs) are rare neoplasm of all astrocytic glial tumors, which occurs commonly in children and young adulthood. We present a case of 75-year male who presented with right side involuntary movements, unconsciousness and tongue bite. On radiological examination CT Scan Head (plain) showed well circumscribed isodense lesion measuring 7.2 x 5.6 x 4.8 cm at the temporoparietal region left side causing displacement of basal ganglia. On histopathological examination, diagnosed as pleomorphic xanthoastrocytoma, of left temporoparietal region. We present this report for its presentation at late age, its clinical, radiological and histomorphological features.